Microalbuminuria as a Predictor of Short-Term Mortality in Acute Ischemic Stroke (Bangladesh Journal of Medical Biochemistry, 2013)
Stroke is one of the major causes of morbidity and mortality all over the world. Microalbuminuria is one of the predictors of mortality. Available published data has suggested that microalbuminuria is a potential new risk factor for ischemic stroke. This study was carried out in the Department of Biochemistry, Dhaka Medical College during the period from July 2009 to June 2010. In this study, we enrolled 120 patients of ischemic stroke. 60 of them were with microalbuminuria (MA) and 60 were without MA. Among the MA +ve group, 38 (63.3%) were males and 22 (36.7%) were females. On the other hand those belonging to MA -ve groups 52 (36.7%) were males and 8 (13.3%) were females. Age range of the subjects in MA +ve group was 45-70 years and in MA-ve group was 50-70 years. In patients with microalbuminuria mortality was 26.7% and in patients without MA mortality was 11.7% (p